1985
DOI: 10.3109/02713688509000852
|View full text |Cite
|
Sign up to set email alerts
|

Localization and properties of an immunoreactive protein in bovine ciliary body similar to retinal S antigen

Abstract: Immunocytochemical studies showed that monoclonal antibodies to bovine retinal S-antigen recognize an immunoreactive protein present in the bovine ciliary body epithelium. This protein was purified by DEAE-agarose chromatography and found to have a M.W. of 28,000 daltons by SDS polyacrylamide gel electrophoresis. Crude and purified preparations of this protein cross-react with polyclonal antibodies to retinal S-antigen. The relative reactivity of S-antigen monoclonal antibodies to ciliary body protein was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Additional studies have also shown the expression in the ocular ciliary epithelium of a visual arrestin (26,27), and the cellular retinaldehyde-binding protein (CRALBP) (28), a component of the visual cycle involved in the transport of 11-cis-retinaldehyde or 11-cis-retinol, retinoid metabolism and visual pigment regeneration (Kennedy et al 1998). These findings are consistent with evidence that the ciliary epithelium and the retina share common genes in part due to their common embryological origin.…”
Section: Discussionsupporting
confidence: 76%
“…Additional studies have also shown the expression in the ocular ciliary epithelium of a visual arrestin (26,27), and the cellular retinaldehyde-binding protein (CRALBP) (28), a component of the visual cycle involved in the transport of 11-cis-retinaldehyde or 11-cis-retinol, retinoid metabolism and visual pigment regeneration (Kennedy et al 1998). These findings are consistent with evidence that the ciliary epithelium and the retina share common genes in part due to their common embryological origin.…”
Section: Discussionsupporting
confidence: 76%